The Role of Higher Education in Promoting Social Mobility in Indonesia - Arifin, Muhammad Husni (European Journal of Social Science Education and Research, 2025)
This paper explains the link between higher education and social mobility in Indonesia. There are several theoretical frameworks talking about the link between higher education and social mobility and the relevant theory of them is Raymond Boudon’s Inequality of Educational Opportunity (IEO) and Inequality of Social Opportunity (ISO). The results reveal that the link between higher education and social mobility in Indonesia is influenced by other factors: inequality of social-economy and geography and cultural disparities. Furthermore, the more decreasing inequality in the society, the more people can go to higher education and in turn will promote upward social mobility.